Hongos endófitos foliares como candidatos a biocontroladores contra iMoniliophthora/i spp. de iTheobroma cacao/i (Malvaceae) en Ecuador (2018)
The adaptability of endophytic fungi to their hosts, the ecological benefits that it provides and the various antagonistic mechanisms against pests make them an alternative for the biological control of diseases. The potential of 17 strains of foliar endophytic fungi (FEF) obtained from healthy Theobroma cacao tissue as candidates for the biological control of Moniliophthora roreri (MR) and M. perniciosa (MP) was determined. We evaluated: i) mycoparasitism of FEF against colonies of Moniliophthora spp., ii) the effects of crude metabolites of FEF on the pathogens´ growth, and iii) the ability to recolonize healthy leaves of the host by leaf assays. Three strains of Lasiodiplodia theobromae were the most promising: Ec098, Ec151 and Ec157. These strains inhibited the growth of MR and MP, both in the confrontation of the colonies and by their metabolites and, additionally, recolonized the host between 80-100 % of the time. Other strains showed outstanding values in one indicator, and not desirable in others. For example, Ec035 (L. theobromae) showed the highest levels of mycoparasitism against both pathogens in the interaction of the colonies, and the second best for its metabolites, but could not reinfect the host. Strain Ec059 (Xylaria feejeensis) reinfected 100 %, but did not show desirable attributes of antagonism. On the other hand, the metabolites of Ec107 (Colletotrichum gloeosporioides s.l.) inhibited MR by 60 %, but also stimulated the growth of MP. No strain achieved all desirable characteristics for a biological control agent.